ANALISIS TINGKAT BRAND AWARENESS DAN STRATEGI OPTIMALISASI PEMASARAN PUPUK NPK KOPI - Lestari, Sri; Yazid, Muhammad; Aryani, Desi (Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Mataram, 2025)
Coffee plantations in South Sumatra face productivity problems that are not optimal. This opens up opportunities for PT Pupuk Sriwidjaja (Pusri) Palembang to develop product innovations, namely NPK Coffee formula 18-8-18 fertilizer specifically for coffee plants. Manufacturers need to know the level of consumer brand awareness to determine the right strategy in marketing their products. This study aims to analyze the level of brand awareness of coffee farmers in Semende Darat Laut towards NPK Kopi Pusri fertilizer and formulate a marketing communication strategy carried out by Pusri in increasing brand awareness with SWOT analysis and analyzing the most optimal marketing communication strategy implemented by Pusri based on the level of brand awareness of coffee farmers in Semende Darat Laut. The results of the analysis showed that the level of brand awareness of coffee farmers in Semende Darat Laut District towards NPK Kopi Pusri fertilizer was in the high category, with the majority of farmers calling this brand spontaneously (top of mind) and most others were able to remember it (brand recall). The strategy that can be implemented is to aggressively expand the market by increasing production capacity, expanding distribution to remote areas, and strengthening promotional activities based on extension and demonstration plots in order to build farmer trust, increase product adoption, and strengthen the brand position in the national coffee fertilizer market.